ANALISIS BIOMEKANIKA GERAK SPRINT MENGGUNAKAN APLIKASI KINOVEA - Steven Natanael Tumanggor; Silvia Fauziah Nasution; M Fikri al Baihaqi Siregar; Kezia Lase; Muhammad Iqbal; Alfi syahri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze kinematic angles in sprint movements using the Kinovea application based on the principles of sports biomechanics. The variables studied include the angles of the hip, knee in the initial phase of the swing, knee at ground contact, ankle at ground contact, ankle at release, and elbow angles. The analysis was carried out by observing video recordings of sprints frame-by-frame, then the measurement results were compared with the theoretical basis of various studies on sprint biomechanics.The analysis findings showed that all analyzed angles were within the ideal range for elite runners accordingto the literature, which proves that the subject's sprint technique is in accordance with biomechanical norms for fast movements. These results indicate that the Kinovea application has proven effective as a means of kinematic analysis in the process of learning and assessing sprint technique.